2019
DOI: 10.1149/2.0231909jss
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Properties of Mg35Sb65/Sb Nanocomposite Multilayer Films for Phase Change Memory Application

Abstract: The phase transition properties of Mg35Sb65/Sb multilayer thin films were studied, including the crystallization mechanism, surface morphology, atomic bonding mode and adhesion strength. With the increase of the thickness of Mg35Sb65 interlayers, Mg35Sb65/Sb thin film had better thermal stability and lower electrical conductivity. The growth-dominated crystallization mechanism made Mg35Sb65/Sb have ultra-fast phase change speed. The subtle change on surface morphology was ascribed to the grain growth and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The point at which the film on the base layer began to delaminate and crack is called the critical point C. The vertical load at point C is defined as the critical load L c , which could quantitatively characterize the bond strength between the film and silicon wafer. 13 As shown in the figure, the critical loads L c of Sb and [Sb(9 nm)/IST(1 nm)] 40 films at annealing temperature 230 °C were 13.1 and 15.8 mN, respectively. The results demonstrated that the bonding strength of the [Sb(9 nm)/IST(1 nm)] 40 film was higher, which might be related to the size shrinkage and density increase in the crystallization process after compositing.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The point at which the film on the base layer began to delaminate and crack is called the critical point C. The vertical load at point C is defined as the critical load L c , which could quantitatively characterize the bond strength between the film and silicon wafer. 13 As shown in the figure, the critical loads L c of Sb and [Sb(9 nm)/IST(1 nm)] 40 films at annealing temperature 230 °C were 13.1 and 15.8 mN, respectively. The results demonstrated that the bonding strength of the [Sb(9 nm)/IST(1 nm)] 40 film was higher, which might be related to the size shrinkage and density increase in the crystallization process after compositing.…”
Section: Resultsmentioning
confidence: 81%
“…The E σ of the amorphous films was about half the value of the band gap E g . 13 Therefore, a wider band gap was obtained after the addition of IST, resulting in better amorphous thermal stability of the phase change film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many attractive features of PCRAM such as high density, high access speed, low power consumption and compatibility with CMOS. [1][2][3][4][5] The data storage capability of PCRAM is based on the phase change material transition between crystalline state (low resistance, set state, data 1) and amorphous state (high resistance, reset state, data 0).…”
mentioning
confidence: 99%